Croatia Health System Quality and Efficiency Improvement : Fiduciary System Assessment - World Bank (Washington, DC, 2014)
A Fiduciary System Assessment (FSA) was carried out in accordance with OP/BP 9.0 that evaluated the fiduciary systems pertaining to the Health System Quality and Efficiency Improvement Program for Results. The integrated fiduciary assessment comprised separate assessments of the fiduciary risks relating to the programs: (i) procurement; (ii) financial management; and iii) governance. The objective of the assessment was to provide reference that could be used to monitor fiduciary system performance during the implementation of the above referenced operation, as well as to identify actions, as relevant, to enhance the performance of the systems. Findings from the assessment, as well as a review of existing analytical and diagnostic work , conclude that the overall fiduciary and governance framework is adequate to support the implementation of Croatia's Health System Quality and Efficiency Improvement Program for Results and includes summary table of the key risks and the corresponding mitigation actions identified. This report is organized along the following lines: presentation of institutional arrangements and national framework; review and assessment of Program fiduciary systems and, including a discussion of baseline performance measurement and indicators, as well as fiduciary risk. While governance and anti-corruption issues are featured prominently throughout the various national systems, institutions, and functions, the report presents these issues in a separate section. Finally, the report includes inputs to the implementation support plan as well as a number of supporting annexes.